A questão agrária e fundiária do sudoeste do Paraná : pequenas propriedade, permanências e rupturas - Orben, Tiago Arcanjo (2019)
This paper discusses several representations of the Paraná state southwestern region by analyzing its agrarian aspects. In this regard, we question the characterization of small properties that is given to the region, mainly concerning the transformations that have taken place over time. One of the most important of these transformations has been intensely researched by the current historiography is the social struggle and it is called the Revolt of the Squatters. Therefore, by researching on documental resources we have observed a meaningful acting of CANGO – National Agricultural Colony General Osório, both as a guidance to the squatters and as a tool for demarcation of land. Hence, we noticed that the Colony had a significant performance between the decades of 1940 and 50 on the agrarian constitution structure concerning the Paraná state southwestern region and this action shapes the model of agriculture and property that was consolidated because of the social uprising of 1957. This research aims to raise questions concerning the actions of the Colony apart from what is commonly known from the region, regarding small properties. As for the land claims, and here we are also using documental references, we observed the actions of the GETSOP – Executive Group for Land Issues from Paraná state southwest. Concerning this institution, our research analyzed its actions inside the region, both regarding its influence on the agrarian structure and, also, the Brazilian modernizing policies on agriculture that have presented new dynamics for the region agrarian issue. By researching archives and oral sources we noticed that the region agrarian structure has been going through several transformations over the years, starting back in 1970 with the Brazilian modernizing policies on agriculture and, contemporarily, when a decrease in the number of small and medium properties takes place, in opposition to the advance of big properties because of the agribusiness and cultures such as the corn and the soybeans. Therefore, this paper aims to discuss the continuities and the ruptures that can be observed inside the agrarian structure in the Paraná state southwestern region.